HUBUNGAN KOMUNIKASI ORANG TUA-ANAK DENGAN STRES AKADEMIK MAHASISWA TAHUN PERTAMA PROGRAM STUDI SARJANA KEPERAWATAN DAN PROFESI NERS FK UNUD - Putu Utami Teja Saraswati; Gusti Ayu Ary Antari; I Kadek Saputra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
First-year students belong to the age of late adolescents who experience emotional instability and are unstable facing problems, so they are more susceptible to academic stress. Academic stress is the biggest factor affecting student academic performance. Family support plays a role in reducing academic stress. The basic foundation for achieving good family support is communication created between parents and children. This research aims to seekkthe relationship of parent-child communicationnwithkacademic stress students of first-year students SchooliofiNursingiFacultyiof MedicineiUdayanaiUniversity. Theumethodkusedninuthis study was correlative with a cross-sectional design. Attotalusampling conducted on 61 students who had met the inclusion and exclusion criteria and analyzed using Pearson Product Moment analysis.nAccordingttotthetstudy thatthastbeentdone, it wasdfoundedythat there wasiaiweakinegative relationshipibetweeniparent-child communication with academic stress (r = -0,363; p-value = 0,004; ? = 0,05). The better parent-child communication, the lower the academic stress experienced by first-year students SchooluofiNursingjFacultyjofiMedicineiUdayanaiUniversity. This study provides an overview of students, parents, and educational institutions to be able to pay attention to students related to academic stress and can improve communication between parents and children.